New York Philharmonic, directed by Arturo Toscanini, concert in Brussels, May 30, 1930 - Société Philharmonique de Bruxelles::::::::::::::: (Belgium; Brussels, 2020)
Program for a concert on May 30, 1930, by the New York Philharmonic conducted by Toscanini, including Beethoven's Eroica Symphony. Includes program notes in French.